The AE889 and AI500 antibodies recognize Klebsiella pneumoniae surface antigens by flow cytometry - Crespo-Yanez, Xenia; Ayadi, Imen (Antibody Reports, 2021)
The recombinant antibodies AE889 and AI500 bind to the surface of the K. pneumoniae 52145 strain as detected by flow cytometry; AI144, AI501, AI502, AI505 and AS733 antibodies do not.